Establishment of Novel Simple Sequence Repeat Markers in Phragmites australis and Application in Wetlands of Nanhui Dongtan, Shanghai - Shaozu Ma; Yifei Shen; Min Li; Ruitong Jiang; Luyi Cai; Tingting Wu; Linxi Gao; Meiqin Wu; Peimin He (Biology)
Common reed (Phragmites australis) is a widely distributed perennial herb of high ecological significance in wetlands worldwide. This research developed 15 SSR markers through whole-genome sequencing and assessed the genetic diversity across four representative reed populations (DB, JPDP, YJRHK, DD) in the coastal wetlands of Nanhui Dongtan, Shanghai. A total of 113.5 alleles (Na) were detected, averaging 7.567 alleles per locus, with an expected heterozygosity (He) of 0.690 and a Shannon diversity index (I) of 1.485. Polymorphism information content (PIC) values (ranging from 0.577 to 0.872, average 0.770) indicated strong resolution power for discriminating subtle genetic differences across populations. Among the four populations, JPDP displayed the highest genetic diversity parameters (Na = 12.667; I = 2.020), whereas DD exhibited the lowest, consistent with intensive demographic screening under saline stress and competition from Spartina alterniflora. Bayesian clustering analysis (STRUCTURE) and UPGMA dendrograms further revealed that the four populations split into two major subgroups, which underlines both the influence of geographic and ecological factors on genetic structuring and the persistence of gene flow. In sum, the newly developed SSR markers demonstrated robustness and sensitivity in elucidating the overall high genetic diversity but moderate genetic differentiation of reed populations in Nanhui Dongtan. These findings not only offer insights into local adaptation mechanisms in coastal wetlands but also provide a technical basis for the conservation and utilization of P. australis.